Vitamin C and Human Health (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Ascorbic acid is a small, simple, water soluble molecule, synthesised by most plants and animals, with the exception of humans and some animal species due to mutations in the gene encoding the terminal enzyme in the biosynthetic pathway. For humans, it is thus a vitamin (vitamin C) that must be obtained from the diet, with complete deficiency resulting in the fatal disease scurvy. Many functions have been attributed to this fascinating molecule and, despite nearly 90 years of research since its discovery, new roles are still being uncovered, including recent discoveries that it acts as a regulator of epigenetic marks and transcription factors (1). In this volume we begin with a review by Michels and Frei on specific factors that need to be taken into consideration when carrying out vitamin C research. Translational research normally comprises a progression from in vitro/cell culture studies to animal models and finally to clinical trials. At each of these stages, there are requirements specific to vitamin C research that need to be integrated into study designs and this review describes these in detail. [...]